The Role of the Substantive Rule in Establishing Civil Protection for Minor: A Descriptive and Analytical Study (Raparin Journal of Humanities (RJH), 2025)
Legal protection is considered an essential element in the formation of rights, such that no legal right can exist without the means for its protection. In other words, the absence of protection makes a legal right nullified, even if it does exist from a moral standpoint. A right remains incomplete unless the community commits to safeguarding it, without such protection the right loses its legal character. Protection, in legal theory, signifies the prevention of people from violating each other’s rights through some specific mechanisms and procedures established by law.It is evident that civil protection constitutes focal point in legal discourse, and the primary emphasis in this subject focuses on one aspect, which is the owner of the right (such as minors). The absence of distinction is a phenomenon present in societies, creating a class with its own legal and sharia characteristics and rulings, which differs from other groups. Since the early stages of legal development, legislations and, prior to that, Islamic law have concerned themselves with this category and established legal texts that define their legal status and regulate their transactions. Legal rules for civil protection of this category of individuals have been established, which provide them with protection by distinguishing them from others, as these rules offer the greatest possible security in preserving their rights and facilitate their reassurance in exercising their rights.